KONTRIBUSI Pratylenchus brachyurus DALAM MENGINDUKSI GEJALA LAYU PADA TANAMAN NANAS (Ananas comosus (L.) Merr) - Lisnawita, Lisnawita; Supramana, Supramana; Suastika, Gede (Jurnal Agroteknos, 2011)
ABSTRACTPineapple is one of the leading export commodities in Indonesia and grown in North Sumatra, South Sumatra, Riau, Bangka, Lampung, West Java and East Java. The main constraint of the cultivation of pineapple is wilt disease caused by plant parasitic nematodes. Research during the years 2008 has been done to study contribution of Pratylenchus brachyurus infection on wilting symptoms induction of pineapple on the pineapple plantation in the Village Bunihayu, Jalancagak district, Subang. The result showed Pratylenchus brachyurus dan P. coffeae (lesion nematode) were the dominant nematodes observed on the location which the community prevalence reached 82.50% and 17.50%. Mapping relationships of nematode populations at various levels of plant growth found that the two nematodes were contributing to the incidence and severity levels of wilt disease, especially in the generative phase of pineapple in the field. Keywords: Pratylenchus brachyurus, pineapple wilt, pineapple (Ananas comosus (l.) Merr)